Strategi Komunikasi Program Jurnal Adhyaksa dalam Edukasi Hukum Publik: Analisis Teori Multimedia Kognitif di Kanal YouTube - Indies, Yasser; Dharmawan, Leonard (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
The Jurnal Adhyaksa program is a public legal education initiative developed by the Attorney General’s Office of the Republic of Indonesia through its YouTube channel. This study aims to analyze the communication strategy applied in the program by referring to communication strategy theory and the Cognitive Theory of Multimedia Learning. A descriptive qualitative approach was employed, utilizing observation of twelve episodes, in-depth interviews, and document analysis. The data were analyzed using the SWOT framework to evaluate the strengths, weaknesses, opportunities, and threats of the communication strategy implemented. The findings reveal that the program has applied most principles of cognitive multimedia, including coherence, signaling, modality, and contiguity, which contribute to the effectiveness of legal message delivery through visual media. The communication strategy also includes the construction of informative, persuasive, and educational messages, along with the use of multiplatform media. However, limitations were identified in content segmentation, audience interactivity, and the adaptation of communication style to Generation Z’s characteristics. These findings highlight the importance of strengthening a more participatory, personalized, and cross-media communication strategy to sustainably support public digital legal literacy.